Develop algorithm for change detection of the salinity from Landsat-8 images - Hasab, Hashim Ali; Ahmad, Anuar; Marghany, Maged; Ziboon, Abdul Razzak (School of Graduate Studies, Universiti Teknologi Malaysia, 2016)
Al-Hawizeh marsh is one of the major marshes southern Iraq. This marsh is covered an area of (2,500-3000) km2. It represents an important water source for peoble and irrigate farmland. The domestic and industrial pollution sources are led to reduction and deterioration of water quality in this marsh. There are approximately 74% of irrigated land are suffering from certain degree of salination. Optical remote sensing sensors such as Landsat-8 (OLI/TIRS) have showed excellent promises for salinity change detection. This is because their abilities to determine spectral signature of any object on the ground and water bodies. The aims of this study to develop mathematical algorithms for the salinity change detection from Landsat-8 images. The integration between remote sensing and geographic information system for retrieving the salinity, spatial variation and distributions within Al-Huwaizah marsh southern Iraq during four seasons in 2013.